Teachers’ perceptions about their own professionalism in the Lejweleputswa district, Free State province, South Africa - Mosoge, Madimetsa; Taunyane, Tlali (University of the Free State, 2012)
Education reform in many parts of the world is premised on the view that teachers show lack of professionalism. The solution to this problem lies in increasing teacher professionalism. Education reform, therefore, affects how teachers view themselves as professionals, their work and their effectiveness, and how they compose their identities in schools. The study aims to investigate the perceptions of teachers with regard to the extent to which they practise professionalism in their schools. The data collected tended to refute the view expressed in the literature that teachers lack professionalism.

Onderwyshervorming in baie dele van die werêld is gebaseer op die siening dat onderwysers ’n gebrek aan professionalisme toon. Die oplossing van probleme in die onderwys lê in die opknapping van onderwyserprofessionalisme. Onderwys-hervorming raak hoe onderwysers hulself as professionele mense, hul werk en hul doeltreffendheid sien en hoe hulle hul identiteit in die skool saamstel. Die studie is gerig op navorsing van die onderwysers se persepsies ten opsigte van die omvang waartoe hulle professionalisme in skole beoefen. Die versamelde data neig om die siening van die literatuur dat onderwysers ’n gebrek aan professionalisme het, te weerlê.
Keywords: Education reform; Teachers; Professionalism